ABCB1 C3435T gene polymorphism as a potential biomarker of clinical outcomes in HER2-positive breast cancer patients. (June 2016) - Madrid-Paredes, Adela; Cañadas-Garre, Marisa; Sánchez-Pozo, Antonio; Segura-Pérez, Ana María; Chamorro-Santos, Clara; Vergara-Alcaide, Esther; Castillo-Portellano, Lucía; Calleja-Hernández, Miguel Ángel
Graphical abstract: Abstract: HER2-positive breast cancer patients treated with trastuzumab schemes have good initial clinical outcomes. Despite this beneficial effect, many patients experiment resistance to these drugs. Several gene polymorphisms in ABCB1, HER2, and CCND1 have been proposed as potential predictors of clinical outcomes of trastuzumab schemes. The aim of this study was to evaluate the association between 4 gene polymorphisms potentially responsible for bad prognosis (HER2-Ile655Val, CCND1-A870G and ABCB1C1236T, C3435T) and clinical outcomes in HER2-positive BC patients. A retrospective cohorts study was performed. Eighty-four HER2-positive BC patients treated with trastuzumab schemes were included. The four gene polymorphisms were analyzed by PCR Real-Time with Taqman ® probes. Genotypes were investigated for their association with tumor response, survival and resistance. Patients with CC genotype of ABCB1-C3435T presented higher risk of resistance to chemotherapy/trastuzumab schemes, compared to those carrying the T-allele (RR: 2.71; CI95%:1.29–5.68; p = 0.013888), progression (RR: 1.89; p = 0.017964); and exitus (RR: 2.09; p = 0.03276). Multivariate logistic regression analysis considering clinical variables and ABCB1-C3435T revealed that the only independent factor associated to resistance to therapy was ABCB1-C3435T gene polymorphism (ORCT/CC: 0.25; p = 0.0123; ORTT/CC: 0.09; p = 0.0348. The protective effect of ABCB1-C3435T T-allele was confirmed in the multivariate Cox regression analysis for PFS (HRCT/CC: 0.41; p = 0.00806; HRTT/CC: 0.22; p = 0.01982) and OS (HRCT/CC: 0.49; p = 0.0555; HRTT/CC: 0.12; p = 0.0398). ABCB1-C1236T, CCND1-A870 G and HER2-Ile655Val polymorphisms were not associated to resistance, PFS or OS (p > 0.05). The A-allele for CCND1-rs9344 was associated with higher response rates (RR: 3.44; uncorrected p-value: 0.03816) in the bivariate analysis, but no statically association was found after Bonferroni correction (p = 0.15264). ABCB1-C3435T, ABCB1-C1236T and HER2-Ile655Val gene polymorphisms were not associated with response. Although this study demonstrates a prognostic value of ABCB1-C3435T gene polymorphism to predict clinical outcomes, further studies with a larger sample will be necessary to validate this result.